Increased Occlusal Vertical Dimension and Its Influence on Lip Position at Smile in Dentulous Adults - Dhyako, N; Mathema, S RB; Shrestha, K; Maharjan, SK; Maskey, B; Gautam, R (Journal of Nepalese Prosthodontic Society, 2023)
Introduction: Increasing occlusal vertical dimension (OVD) is often indicated in complex prosthodontic rehabilitations to gain restorative space and improve the occlusal relationship and esthetics. However, any alterations made in OVD will also influence the lip position mainly during rest and smile. This study aims to determine the influence of the vertical dimension of occlusion on lip positions at a smile.Methods: 30 samples between the age group of 20 - 30 years were included in this study meeting the selection criteria. The acrylic splint of varying thicknesses of +2mm, +4mm, +6mm, +8mm was prepared on the dental stone cast of a patient that was articulated in a semi-adjustable articulator after tentative facebow transfer. Smile photograph of each individual at the occlusal vertical dimension of +0mm, +2mm, +4mm, +6mm, +8mm was taken using a DSLR camera mounted on a tripod using the prepared acrylic splints. Digital measurements were done in photographs using the Adobe Photoshop software.Results: The study's results demonstrate that increasing the OVD significantly affects the inter labial distance, incisal edge to lower lip distance, and the display zone area. However, the study found no notable alterations in the distance from the incisal edge to the upper lip or in the intercommissural width with the same increased OVD. These findings demonstrate on how changes in OVD can influence various orofacial measurements.Conclusion: Within the limitation of this study, it can be concluded that with the increase in the OVD, inter labial distance, incisal edge to lower lip distance, and display zone area are increased. But upper lip position and inter commissural width should not be expected to be changed with increased OVD.